Contribution of the Open Access Modality to the Impact of Hybrid Journals Controlling by Field and Time Effects - Dorta-González, Pablo; Dorta-González, María Isabel (Journal of data and information science (Warsaw, Poland), 2022)
Researchers are more likely to read and cite papers to which they have access than those that they cannot obtain. Thus, the objective of this work is to analyze the contribution of the Open Access (OA) modality to the impact of hybrid journals.The “research articles” in the year 2017 from 200 hybrid journals in four subject areas, and the citations received by such articles in the period 2017–2020 in the Scopus database, were analyzed. The hybrid OA papers were compared with the paywalled ones. The journals were randomly selected from those with share of OA papers higher than some minimal value. More than 60 thousand research articles were analyzed in the sample, of which 24% under the OA modality.We obtain at journal level that cites per article in both hybrid modalities (OA and paywalled) strongly correlate. However, there is no correlation between the OA prevalence and cites per article. There is OA citation advantage in 80% of hybrid journals. Moreover, the OA citation advantage is consistent across fields and held in time. We obtain an OA citation advantage of 50% in average, and higher than 37% in half of the hybrid journals. Finally, the OA citation advantage is higher in Humanities than in Science and Social Science.Some of the citation advantage is likely due to more access allows more people to read and hence cite articles they otherwise would not. However, causation is difficult to establish and there are many possible bias. Several factors can affect the observed differences in citation rates. Funder mandates can be one of them. Funders are likely to have OA requirement, and well-funded studies are more likely to receive more citations than poorly funded studies. Another discussed factor is the selection bias postulate, which suggests that authors choose only their most impactful studies to be open access.For hybrid journals, the open access modality is positive, in the sense that it provides a greater number of potential readers. This in turn translates into a greater number of citations and an improvement in the position of the journal in the rankings by impact factor. For researchers it is also positive because it increases the potential number of readers and citations received.Our study refines previous results by comparing documents more similar to each other. Although it does not examine the cause of the observed citation advantage, we find that it exists in a very large sample.